Experimental investigation of the effect of diameter ratio on velocity ratio and pressure gradient for the spherical capsule train flow - Ulusarslan, Deniz (ELSEVIER, 2013)
The study deals with experimental investigation of the effect of diameter ratio on velocity ratio and pressure gradient for the spherical capsule train with density lower than that of water conveyed by water in a horizontal pipe of diameter 0.1 m. Two different capsule diameters (d = 0.08 and 0.072 m) were investigated. Measurements were conducted on capsule concentrations of 5%-20% at bulk velocities ranging from 0.2 to 1.0 m/s. The effect of the bulk velocity and diameter ratio on the velocity ratio was demonstrated. The velocity ratio increased with decreasing diameter ratio and capsule concentration. The capsule velocity increases with increasing bulk velocity, however at the same bulk velocity the increase of the velocity of the capsule train with smaller diameter ratio is higher. The effect of the different diameter ratio on the pressure gradient was found negligible. (C) 2012 Elsevier Masson SAS. All rights reserved.
Keywords: Spherical capsule train; Capsule pipelining; Velocity ratio; Pressure gradient; Diameter ratio; PIPELINE FLOW; TRANSPORT; WATER; SHAPE; Mechanics; Physics